P-323 Should We Measure Oxidative Stress Biomarkers In Follicular Fluid Of Women With Endometriosis Undergoing IVF?. (30th June 2022) - Gupta, P; Malhotra, N; Dada, R
Abstract: Study question: Do levels of Oxidative stress (OS) biomarkers differ in the follicular fluid of women with endometriosis compared to tubal factor infertility? Summary answer: 8-Isoprostane is a promising biomarker in diagnosing oxidative stress in women with endometriosis opening a window of opportunity for improving outcomes. What is known already: A delicate balance between oxidants and antioxidants is required for oocyte development and maturation. Any perturbation in the oocyte microenvironment which is the follicular fluid results in hampered oocyte quality and further affects the embryo development. As endometriosis causes destruction of the oocyte milieu, various OS biomarkers have been explored with inconclusive results. The present study aimed to compare these biomarkers in follicular fluid of women with endometriosis and tubal factor infertility undergoing in-vitro fertilization and correlate with ART outcomes. Study design, size, duration: In a cross sectional study conducted at the assisted conception unit at a tertiary care hospital from 2017-2018 women undergoing their first IVF cycles for endometriosis and tubal factor infertility were recruited in the study. The study included a total of 107 patients with 50 in the endometriosis group (Group1) and 57 in the tubal group (Group 2). Participants/materials, setting, methods: Follicular fluid from women undergoing IVF in both the groups was collected and evaluated for Oxidative stress biomarkers including Reactive Oxygen species (ROS), Total Antioxidant Capacity (TAC), 8-Isoprostane (8-IP) levels. ROS levels were detected by chemiluminescence and TAC and 8-IP using enzyme immunoassays. Main results and the role of chance: Levels of ROS {(39.6 cpm vs 54.8 cpm) (p = 0.2)}were comparable in both the groups. Levels of 8-IP were significantly higher in group 1 as compared to the group 2 {(85.2  pg/ul vs 39.2  pg/ul) (p = 0.01)}. TAC levels were higher in endometriosis group compared to the tubal group {(5.4 mM of Trolox vs 4.1 mM of Trolox) (p = 0.005)} which could explain comparable ongoing clinical pregnancy rate in both groups (24.0% vs 24.5%, p = 0.34). There was no correlation of OS biomarkers with ART outcomes in tubal factor. Follicular fluid in Group 1 revealed a negative correlation of ROS with cleavage rate (r = - 0.42, p = 0.002) and positive correlation of TAC with fertilization rate (r = 0.44, p = 0.001) and Good grade embryos (r = 0.4, p = 0.001). Limitations, reasons for caution: The main limitation is the inability to assess the dietary intake and blood oxidative stress biomarkers in both the groups. Wider implications of the findings: OS biomarkers especially 8-IP could be useful in prognosticating IVF outcomes in women with endometriosis with a potential role of addition of antioxidants in culture media during IVF in these women. Trial registration number: Not Applicable